PERAN FINTECH PEMBAYARAN DAN P2P LENDING TERHADAP PENDAPATAN UMKM PASCA PANDEMI COVID-19 - Fitri Seftiyati; Tiara Nirmala (Yayasan Education and Social Center, 2026)
Following the Covid-19 pandemic, the use of financial technology has become essential to MSMEs' rehabilitation and expansion. This study looks at how P2P loan fintech (SPayLater) and payment fintech (ShopeePay) help MSMEs in Bandar Lampung boost their revenue through the Shopee app. The study uses a quantitative descriptive methodology, gathering information via surveys, interviews, documentation, and observations. The findings show that although SPayLater offers rapid access to funds for stock expansion and cash flow support, ShopeePay expedites transactions, streamlines financial record-keeping, and boosts customer numbers. When combined, these financial solutions build a digital environment that boosts MSME income after the epidemic. In order to help MSMEs become more competitive and adaptable, the study offers suggestions for the government, e-commerce platforms, and MSMEs to improve fintech literacy and digital strategies.